Use of Aspiration Funds of The Council of Representatives; Study on Constitutional Court Decision Number 106/PUU-XIII/2015 - Putra Nur Fikri; Masyrofah Masyrofah (UIN JAKARTA, 2021)
The background to this research is that Article 80 Letter J of Law Number 17 of 2014 has been reviewed by the Indonesian Constitutional Court. The Petitioner in this case represents the people of Papua, who believe their constitutional rights have been violated because the petition will result in unfair management of state finances that benefits only the people in the area chosen to have the most seats in the House of Representatives. However, the Constitutional Court rejected the request brought against article 80 letter j in decision 106/PUU-XIII/2015. This research employs normative legal analysis by collecting data from the Research Library, which examines relevant documents. The findings of this study indicate that the use of aspiration funds as defined in Article 80 Letter J of Law Number 17 of 2014 does not reflect people's justice, as the allocation of aspiration funds is unfair, as it is based on electoral districts and the number of House of Representatives seats. Individuals within an area are not identical, which may result in development injustice.